Education Management using Blockchain as Future Application Innovation - Maulani, Giandari; Musu, Eng. Wilem; Soetikno, Y. Johny W.; Aisa, Sitti (Pandawan Sejahtera Indonesia, 2021)
This paper means to give a precise writing audit on blockchain innovation in training to offer a definite comprehension of the current situation as far as advantages, boundaries, current uses of blockchain innovation and future regions where blockchain innovation can be carried out in different spaces of schooling. A bibliometric investigation was performed for information in distributions, diaries, creators and gathered references, and checked by applying bibliometric measures. The investigation shows that blockchain innovation in schooling is as yet a youthful discipline, yet has a great deal of potential to help the training area on the loose. This examination gives an establishment to instructive organizations, strategy creators and specialists to investigate different regions where blockchain innovation can be executed, albeit this exploration additionally recommends some potential employments of blockchain innovation in different elements of the training framework, more applications can be brought into the schooling framework to exploit the capability of blockchain innovation. This paper examines the use of blockchain in innovation in schooling with the assistance of bibliometric examination. This is one of the main realized investigations to survey blockchain innovation by distinguishing the current advantages, boundaries, and utilizations of blockchain innovation.